Generation Y: the development and use of shopping lists - Arnaud, Alexandre; Kollmann, Alexandra; Berndt, Adele (Advances in Social Sciences Research Journal, 2015)
Grocery shopping is one of the most basic elements of consumer behaviour and is a part of everyday life. For consumers to achieve their goals and make their grocery shopping trip efficient, many plan their shopping trip, as seen in the development and use of a shopping list. Previous studies have taken a general view of consumers and not investigated any one specific cohort. Generation Y is regarded as an important and knowledge cohort, with greater access to information and resources yet the development and use of shopping lists among this cohort is largely unknown. The purpose of this study is thus to understand the development and usage of shopping lists by Generation Y consumers. Use was made of a qualitative method to understand the development, usage and outcomes associated with list usage among this cohort. In total, 29 personal semi-structured interviews were conducted with interviews in supermarkets, the university or at the participants’ house. The findings show that the majority of Generation Y consumers develop and use shopping lists, and use both paper and electronic lists. The purpose for their development is for reminding, planning and saving money. The respondents believe that lists help reduce unplanned purchases, as well as reducing the time spent and cost in store. Grocery shopping is one of the most basic elements of consumer behaviour and is a part of everyday life. For consumers to achieve their goals and make their grocery shopping trip efficient, many plan their shopping trip, as seen in the development and use of a shopping list. Previous studies have taken a general view of consumers and not investigated any one specific cohort. Generation Y is regarded as an important and knowledge cohort, with greater access to information and resources yet the development and use of shopping lists among this cohort is largely unknown. The purpose of this study is thus to understand the development and usage of shopping lists by Generation Y consumers. Use was made of a qualitative method to understand the development, usage and outcomes associated with list usage among this cohort. In total, 29 personal semi-structured interviews were conducted with interviews in supermarkets, the university or at the participants’ house.The findings show that the majority of Generation Y consumers develop and use shopping lists, and use both paper and electronic lists. The purpose for their development is for reminding, planning and saving money. The respondents believe that lists help reduce unplanned purchases, as well as reducing the time spent and cost in store.